The Effective Radiation Pattern Concept for Realistic Performance Estimation of LTE Wireless Systems. (13th November 2013) - Zarbouti, Dimitra; Tsoulos, George; Athanasiadou, Georgia; Valagiannopoulos, Constantinos
Abstract : Radio channels induce distortions to the radiation pattern of beamforming systems such as beam broadening as well as sidelobe level and null rising. If these effects are ignored, the system performance is overestimated. This paper proposes the simple concept of an effective radiation pattern (ERP) calculated by optimally fitting the "real-world" radiation pattern to the ERP. The proposed ERP method is incorporated into a multicell bad urban 4G LTE operational scenario which employs beamforming for both the BSs and the RNs. The performed simulations provide evidence that the ideal instead of the real radiation pattern overestimates the SIR and capacity by almost 3 dB and 13 Mbps, respectively, for the reference scenario without RNs. It also proves that the ERP method produces almost identical performance results with the real radiation pattern, and hence it is a simple and viable option for realistic performance analysis. Finally, the network performance is studied as a function of the number of RNs with the help of the ERP method. Results show that a beamforming LTE network with RNs that also employ beamforming provides 3 dB SIR gain with the addition of 1 RN per cell and 15 dB gain with 4 RNs per cell.